CLINICAL EXPERIENCE OF OXYTOCIN USE DURING SPONTANEOUS LABOR: A SURVEY OF MIDWIVES’ PRACTICES IN THE BASIC MATERNITY UNITS OF KINDU - Alain, Bakangana Mungu; Onyango O, Rosebella; Bogren, Malin (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
The administration of oxytocin during spontaneous labor is a common practice in the maternity hospitals of Kindu, but its practice by midwives in the province of Maniema in general and in the city of Kindu in particular is still problematic. The objective of this study was to identify the usual practices of midwives in Kindu maternity hospitals regarding the use of oxytocin during spontaneous labor. This was a descriptive cross-sectional study of 14 practicing midwives working in five maternity hospitals in Kindu, Maniema Province in Democratic Republic of Congo. We considered all of their staff because of their limited number (n = 14). This was an exhaustive non-probability sample. Inclusion criteria - Being a midwife; - To work in one of the maternity units targeted by the study Any provider not meeting these criteria was not included in the study. Data were collected using a questionnaire with 9 open and closed questions, encoded on Excel sheets and exported to STATA 14 software and processed using relative frequency calculations (percentages). Through this study, we found that midwives in the basic maternity hospitals of Kindu were performing acts contrary to the recommended scientific standards for the use of oxytocin during spontaneous labor. The vast majority of them (92.86%) did not know what to do in the event of cervical changes and/or 5 uterine contractions per 10 minutes; did not record the indication for oxytocin administration in the obstetrical record (78.57%); did not have a protocol for oxytocin use in their maternity units (57.14%) and did not have appropriate equipment for oxytocin administration